2010
DOI: 10.1165/rcmb.2009-0025oc
|View full text |Cite
|
Sign up to set email alerts
|

Aging Enhances Susceptibility to Cigarette Smoke–Induced Inflammation through Bronchiolar Chemokines

Abstract: Cigarette smoking and aging are major risk factors for chronic obstructive pulmonary disease. An unsolved question is whether elderly lungs are particularly vulnerable to cigarette smoke (CS) exposure. In this study, we used a mouse model to test the hypothesis that aging increases the susceptibility to CS-induced pulmonary inflammation. We subjected 9-week-old and 69-week-old C57BL/6J mice to CS (whole-body exposure, 90 min/d), and evaluated neutrophil infiltration in the lungs, the levels of keratinocyte-der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
1

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
1
23
1
Order By: Relevance
“…This progression parallels persisting inflammatory responses (83), suggesting that additional mechanisms must account for the consolidation of the disease in genetically susceptible hosts, often after decades of active smoking ( Figure 1). This change in the nature of inflammation in the course of disease is highlighted by the temporary nature of NF-κB activation in rodent lungs exposed to cigarette smoke (84). Two paradigms have emerged that might explain some of these observations: autoimmunity (52) and lung aging (85).…”
Section: Consolidationmentioning
confidence: 99%
“…This progression parallels persisting inflammatory responses (83), suggesting that additional mechanisms must account for the consolidation of the disease in genetically susceptible hosts, often after decades of active smoking ( Figure 1). This change in the nature of inflammation in the course of disease is highlighted by the temporary nature of NF-κB activation in rodent lungs exposed to cigarette smoke (84). Two paradigms have emerged that might explain some of these observations: autoimmunity (52) and lung aging (85).…”
Section: Consolidationmentioning
confidence: 99%
“…It has been reported that older mice develop a greater inflammatory response, either spontaneously or after smoke exposure, compared to young mice ([8][10], and see Discussion), and conversely, a decreased antioxidant response [10], [11]. However, whether older animals actually develop worse COPD compared to younger has not been examined.…”
Section: Introductionmentioning
confidence: 95%
“…COPD is characterized by destruction of alveolar wall, inflammatory response, and premature lung aging or cellular senescence (Nyunoya et al, 2006; Moriyama et al, 2010; Yao et al, 2012; Ahmad et al, 2015). Pro-inflammatory mediators such as IL-8 (mouse KC) and MIP-2, act as CXCR2 ligands, which are critical for recruitment of peripheral neutrophils.…”
Section: Introductionmentioning
confidence: 99%